Developmental Abilities to Form Chunks in Immediate Memory and Its Non-Relationship to Span Development - Mathy, Fabien; Fartoukh, Michael; Gauvrit, Nicolas; Guida, Alessandro (Frontiers in Psychology, 2016)
Both adults and children --by the time they are two to three years old-- have a general ability to recode information to increase memory efficiency. This paper aims to evaluate the ability of untrained children aged six to ten years old to deploy such a recoding process in immediate memory. A large sample of 374 children were given a task of immediate serial report based on SIMON, a classic memory game made of four colored buttons (red, green, yellow, blue) requiring players to reproduce a sequence of colors within which repetitions eventually occur. It was hypothesized that a primitive ability across all ages (since theoretically already available in toddlers) to detect redundancies allows the span to increase whenever information can be recoded on the fly. The chunkable condition prompted the formation of chunks based on the perceived structure of color repetition within to-be-recalled sequences of colors. Our result shows a similar linear improvement of memory span with age for both chunkable and non-chunkable conditions. The amount of information retained in immediate memory systematically increased for the groupable sequences across all age groups, independently of the average age-group span that was measured on sequences that contained fewer repetitions. This result shows that chunking gives young children an equal benefit as older children. We discuss the role of recoding in the expansion of capacity in immediate memory and the potential role of data compression in the formation of chunks in long-term memory.